CREATIVE ENVIRONMENTAL ENERGY TECHNOLOGY ASSESSMENT HYDROELECTRIC POWER PLANT (CASE STUDY OF WONOGIRI RESERVOIR) - Feby Hidayani; Yohanes Sardjono; Chafid Fandeli; Rukmini A.R (Indonesian Journal of Physics and Nuclear Applications, 2017)
Hydroelectric power plants in Indonesia are widely developed. This is because the water supply in Indonesia is quite abundant. Several large reservoirs in Indonesia, in addition to being used for water reservoirs, are used to produce electricity. Wonogiri is a region that is located in Central Java province, where most of the region is arid land that cannot be planted in the dry season. In the rainy season the abundance of water plants to die and the soil is such that in the dry season crops do not grow well. Plans for the construction of Gajah Mungkur started in 1964, and it is designed to be a multipurpose dam project that aim to control floods, supply water for irrigation and hydropower in the Solo River valley. The master development plan was formulated in 1972-1974 with the help of Overseas Technical Cooperation of Japan. The results of this study include the completion of flooding problems along the Solo River, the increase in agricultural output in Winton community with irrigation facilities and good infrastructure, availability of electricity for communities around the dam and improving the local economy as the development of inland fisheries and tourism sectors.